Social Interaction in the Context of Educational and Social Reforms. - Ivanchenko, Svitlana M. (Psychological Prospects Journal, 2017)
Social psychological support for social reforms is aimed at organization of interaction and dialogue among all the concerned parties. A very broad understanding of the notion “social interaction” demands its restricting for the following usage as the central element of social psychological support for educational and social reforms. Social psychological approaches to social interaction are viewed in two dimensions: as a direct “face-to-face” communication, and as a social networks mediated communication. Up-to-date is an organization of social-psychological support aimed at the support of the educational reform at both social level and the educational settings. The paper is aimed at searching for the methods of interaction of collective subjects in a process of social psychological support for educational reform, and presentation of the experimental study outcomes. The experimental study based on the integrated system of technologies in the context of social support of educational reform is presented. Contrary to the standard public opinion polls (that fix existing opinions), this technology was shaped for forming the opinion through deliberation, consolidation, promotion, and creation of social networks. The results of the first stage of the experimental study – entry monitoring and online poll − are described. Next stage will be an interaction of participants – teachers, students, and their parents – with using the social psychological technologies (public opinion deliberation, consensus method, networking, reflexive management, innovative culture).Key words: educational reform, integrated system of technologies, social interaction, social psychological support, public opinion.